2012
DOI: 10.3390/ijms13044642
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Proteins Associated with Periodontitis in Patients with Type 2 Diabetes Mellitus

Abstract: The objective of this study was to investigate the salivary proteins that are associated with periodontitis in patients with Type 2 diabetes mellitus (T2DM). Volunteers for the study were patients from the Diabetic Unit, University of Malaya Medical Centre, whose periodontal status was determined. The diabetic volunteers were divided into two groups, i.e., patients with periodontitis and those who were periodontally healthy. Saliva samples were collected and treated with 10% TCA/acetone/20 mM DTT to precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 48 publications
3
36
1
2
Order By: Relevance
“…There were no significant differences between the groups (n.s; p > 0.05). and serum L-plastin levels in chronic periodontitis were numerically higher than in health, this difference did not reach statistical significance, which could be in agreement with a recent report in diabetic patients, showing elevated L-plastin salivary levels in chronic periodontitis compared with periodontal health (27). Although the findings from the present cohort of patients suggest that serum and salivary L-plastin levels cannot be used to distinguish between periodontal diagnoses, a larger patient sample size would be required to reach a more definitive conclusion.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…There were no significant differences between the groups (n.s; p > 0.05). and serum L-plastin levels in chronic periodontitis were numerically higher than in health, this difference did not reach statistical significance, which could be in agreement with a recent report in diabetic patients, showing elevated L-plastin salivary levels in chronic periodontitis compared with periodontal health (27). Although the findings from the present cohort of patients suggest that serum and salivary L-plastin levels cannot be used to distinguish between periodontal diagnoses, a larger patient sample size would be required to reach a more definitive conclusion.…”
supporting
confidence: 84%
“…Although the L-plastin levels were similar between the two forms of periodontitis, this does not necessarily imply that this molecule plays a similar role in the pathogene-sis of both diseases. This similar expression pattern in gingival tissues could be the result of similar chronic infiltrate patterns in both types of periodontitis lesions (27)(28)(29)(30)(31). Recent gingival tissue transcriptome data also confirm that generalized aggressive periodontitis and chronic periodontitis are very similar at the molecular level (32).…”
mentioning
confidence: 70%
“…High levels of the selective APPs in the saliva of the betel quid chewers may possibly be due to mucosal inflammation or premalignancy. However, since the levels of saliva AAT, C3, HPX, TTR, ABG, and HAP were not previously reported to be significantly altered in patients with periodontitis , their change of abundance in the saliva of the betel quid chewers detected in the present study is suggestive of its likely association with precancerous conditions.…”
Section: Discussionsupporting
confidence: 41%
“…Based on the diabetes atlas, the highest numbers of patients are currently found mainly in western countries, such as in the European region and the Western Pacific region. This, however, will change in the year 2025 where the greatest number of diabetic patients is expected to be from the Asian region [5]. A recent clinical study showed that gingival bleeding is significantly increased in children with poorly controlled type 1 diabetes compared with nondiabetic controls [9].…”
Section: Introductionmentioning
confidence: 99%